Colorectal Cancer: How Familiar Are Our Future Doctors with the Cancer of Tomorrow?. (5th June 2018) - Kulkarni, Vaman; Darshan, B. B.; Unnikrishnan, Bhaskaran; Cheng, Kho Chun; Hui, Goh Cia; Theng, Ang Yee; Yuien, Kong Sik; Thapar, Rekha; Mithra, Prasanna; Kumar, Nithin; Holla, Ramesh; Kumar, Avinash
Abstract : Background . Colorectal cancer (CRC) is one of the common cancers affecting both genders. Although the incidence of CRC is low in India there has been an increase in the past few decades. Objective . To assess the awareness regarding colorectal cancer and its screening among medical students and interns. Methods . This cross-sectional study was conducted among 290 participants (final year medical students and interns) from Kasturba Medical College, Mangalore. A pretested semistructured questionnaire was used to collect information. Data was analyzed using SPSS 17.0. Results . Majority of participants had satisfactory knowledge regarding CRC. 38% of them scored excellently, 64.8% had good knowledge, and 5.2% scored poorly. Knowledge regarding CRC symptoms was good (95%). 92% of the participants were aware of risk factors of CRC. Only 49% of the participants identified FOBT as a screening tool and 30.7% participants knew that 50 years is the recommended age to begin CRC screening. Interns and international students had better knowledge than final year medical students and Indian students and this was found to be statistically significant. Conclusion . There is a need to improve participant's knowledge regarding CRC screening although majority of them are aware of CRC symptoms and risk factors.